Intracellular signalling pathways: targets to reverse immunosenescence. (3rd August 2016) - Fulop, T.; Witkowski, J. M.; Le Page, A.; Fortin, C.; Pawelec, G.; Larbi, A.
Summary: Ageing is a very complex process, the result of the dysregulation of multiple systems interacting in many ways. A prominent change occurring with ageing is related to the architecture and functioning of the immune system, viewed commonly as detrimental and termed 'immunosenescence'. However, age‐associated changes may also lead to increased function in certain respects, which can be viewed as adaptive. None the less, on balance it is well‐recognized that immunosenescence is accompanied by the low‐grade inflammation observed commonly in elderly people, which has been dubbed 'inflamm‐ageing'. The exact cause and significance of all these changes is not clear, but there is a consensus that they are related to the occurrence of chronic non‐infectious age‐associated disease, as well as increased susceptibility to infections. Alterations to immune cell signalling may be a prominent cause of malfunctioning immunity. Emerging attempts to reverse immunosenescence have recently targeted the signalling pathways in various different cell types of the immune system. Here, we review and discuss alterations in the signalling pathways of immune cells with ageing and consider current targets and means to modulate altered functions. We discuss the potential dangers as well as the benefits of these interventions, and consider future approaches to this problem. Abstract : Alterations to immune cell signaling may be a prominent cause of malfunctioning immunity with aging. Emerging attempts to reverse immunosenescence have recently targeted the signaling pathways in various different cell types of the immune system. Here, we review and discuss alterations in the signaling pathways of immune cells with aging and consider current targets and means to modulate altered functions.